Life history of the Pomadasys incisus (Osteichthyes: Haemulidae) of the Canarian Archipelago - Pajuelo, José G.; Lorenzo, José M.; Gregoire, Muriel; Domínguez-Seoane, Rosa (Scientia Marina, 2003)
Pomadasys incisus is one of the most abundant coastal demersal species around the Canary Islands. It is a gonochoric species with similar biological characteristic in males and females. The adult sex ratio is not significantly different from 1:1, and the mean size of males and females is similar. It reaches first maturity at the end of the second year of life (183 mm). Spawning takes place throughout the year. Growth analysis reveals that the species is fast-growing and relatively short-lived (7 years). Length at age is well described by the von Bertalanffy growth model. Individuals grow quickly in their immature first year, attaining approximately 45% of their maximum length. After one year, the annual growth rate drops rapidly. The direct effects of fishing result in changes in abundance, with an 80% reduction from the unexploited equilibrium level. Recruitment into the commercial fisheries occurs before size at sexual maturity, resulting in all spawners being accessible using the current fishing pattern. The length at first capture (168 mm) is less than the length at maturity; 45% of the total catch are smaller than this, indicating a danger of recruitment-overfishing.